Pembuatan Aplikasi Informasi Beasiswa Berbasis Android - Sharlyne Sinsky Hendra; Andreas Handojo; Anita Nathania Purbowo (Jurnal Infra, 2018)
Scholarships are grants in the form of financial help to anyoneeligible based on the given requirements and are used to ensuretheir education sustainability. School and university students oftensearch for information on scholarships which are obtainable frombroadcast news on social media, brochures, wall magazines, andother mass media.However, as the information they get is disorganised as it isobtained from different sources, they may find it difficult to getupdated on the specific information they have gotten. Anotherproblem related to different sources of scholarship information isthat both school and university students face difficulties tocompare every piece of scholarship information to choose the bestone.Therefore, the development of this Android-based scholarshipinformation application will help its users to easily getinformation on scholarships. The users will get notified whenthere is newest information on scholarships and will be able tosearch and get suggested scholarships according to the users'sprofile information.